Pre-test characteristics of unstable angina patients with obstructive coronary artery disease confirmed by coronary angiography - Fladseth, Kristina; Kristensen, Andreas; Mannsverk, Jan; Trovik, Thor; Schirmer, Henrik (Open Heart, 2018)
Objective : Patients referred for acute coronary angiography (CAG) with unstable angina (UA) have low mortality and low rate of obstructive coronary artery disease (CAD). Better pre-test selection criteria are warranted. We aimed to assess the current guidelines against other clinical variables as predictors of obstructive CAD in patients with UA referred for acute CAG. Methods : From 2005 to 2012, all CAGs performed at the University Hospital of North Norway, the sole provider of CAG in the region, were recorded in a registry. We included 979 admissions of UA and retrospectively collected data regarding presenting clinical parameters from patient hospital records. Obstructive CAD was defined as ≥50% stenosis and considered prognostically significant if found in the left main stem, proximal LAD or all three main coronary arteries. Characteristics were analysed by logistic regression analysis. A score was developed using ORs from significant factors in a multivariable model. Results The overall rate of obstructive CAD was 45%, and the rate of prognostically significant CAD was 11%. The risk criteria recommended in American College of Cardiology/American Heart Association and European Society of Cardiology guidelines had an area under the curve (AUC) of 0.58. Adding clinical information increased the AUC to 0.77 (95% CI 0.74 to 0.80). Applying the derived score, we found that 56% (n=546) of patients had a score of <13, which was associated with a negative predictive value of 95% for prognostic significant CAD. Conclusions : The current results suggest that CAG may be postponed or cancelled in more than half of patients with UA by improving pre-test selection criteria with the addition of clinical parameters to current guidelines.